The diverse manifestations of tuberous sclerosis complex: the experience of a provincial TSC clinic. (3rd June 2015) - Wilbur, C; Sanguansermsri, C; Chable, H; Mihaela, A; Connolly, MB
Abstract : Background: Recent consensus recommendations for Tuberous Sclerosis Complex (TSC) stress the importance of multidisciplinary follow-up for these patients. The objective of our study was to review the manifestations of TSC seen in our hospital to determine the care needs of this population. Methods: This was a systematic, retrospective chart review of children with TSC treated at our institution. Patients were identified through epilepsy and clinical neurophysiology databases. Results: The study population comprised 81 patients, born between 1987-2014, who were a median 10 (Range 0.2-23.2) years of age at last follow-up. 88% of patients had epilepsy, including 30% with a history of infantile spasms. Developmental delay was reported in 65%, while 40% had intellectual disability. Psychiatric co-morbidities occurred in 49%. The most common psychiatric diagnoses were autism (25%), ADHD (19%), and anxiety (16%). Cardiac rhabdomyomas occurred in 35% of patients and renal angiomyolipomas in 42%, while only 4% had polycystic kidneys. Subependymal giant cell astrocytomas were observed in 14% of patients. 86% had skin manifestations. Conclusions: This study reaffirms the multi-system manifestations of TSC and the need to provide comprehensive, multidisciplinary care. As many children are still very young, the prevalence of autism and intellectual disability is likely underestimated.